Winterstar™ (‘FL 05-107’) Strawberry - Vance M. Whitaker; Craig K. Chandler; Bielinski M. Santos; Natalia A. Peres (EDIS)
Winterstar™ (‘FL 05-107′) is a new strawberry cultivar released from the University of Florida in 2011, originating from a 2005 cross between ‘Florida Radiance’ and ‘Earlibrite’. Data from several years of trials were used to generate this information and recommendations to help growers obtain optimal performance in West Central Florida. This 3-page fact sheet was written by Vance M. Whitaker, Craig K. Chandler, Bielinski M. Santos, and Natalia A. Peres, and published by the UF Department of Horticultural Sciences, April 2012.